Help for the child with Asperger's Syndrome : a parent's guide to negotiating the social service maze - Mertz, Gretchen, 1959- (Jessica Kingsley Publishers, 2005)
Parents of children diagnosed with Asperger's Syndrome frequently find themselves embarking on an exhausting and disheartening hunt for the services and interventions that their child needs - and is entitled to. Gretchen Mertz presents a readable and comprehensive parent's guide to developing an intervention program for a child with AS. Beginning with the search for a diagnosis, she outlines an accessible overview of the helpful and appropriate services that are available, how to find them and get funding for them, what to expect of them, and how to evaluate them. The issues raised and the inf.